ANALISIS KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK DENGAN MEMANFAATKAN LINGKUNGAN PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 6 PALEMBANG - Yeyen Febrianti; Yulia Djahir; Siti Fatimah (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2016)
This study discussed about the students creative thinking ability to use the environment on economic subject at SMA Negeri 6 Palembang. The problem of this study was how the students creative thinking ability to use the environment on economic subjects at SMA Negeri 6 Palembang ?. The variables of this study were creative thinking and the environment. This study used descriptive method. The sample was 53 students at SMA Negeri 6 Palembang. The data were collected by observation, interview, and documentation. The result from observation showed that the creative thinking of students consisted of five indicators, they were fluent skill with the very well criteria (83.76%), flexible skill with the very well criteria (89.1%), original skill with the good criteria (79.25%). It was suggested to economic teachers to develop the detail skills that had good criteria became very good criteria, so that students were able to develop an idea in detail which was further improved.